2009
DOI: 10.1583/08-2652.1
|View full text |Cite
|
Sign up to set email alerts
|

Primary Cryoplasty Therapy Provides Durable Support for Limb Salvage in Critical Limb Ischemia Patients With Infrapopliteal Lesions:12-month Follow-up Results From the BTK Chill Trial

Abstract: Cryoplasty therapy is a safe and effective method of treating infrapopliteal disease, providing excellent results and a high rate of limb salvage in patients with CLI. Study outcomes through 1 year support the use of cryoplasty as a primary treatment option for patients with CLI secondary to BTK occlusive disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
29
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(29 citation statements)
references
References 49 publications
0
29
0
Order By: Relevance
“…In contrast, 12-month follow-up results from the BTK Chill Trial, which evaluated cryoplasty in the infrapopliteal arteries of CLI patients, reported high rates of acute technical success and major amputation-free interval (97.3% and 78.5%, respectively) followed by a low percentage of clinically driven repeat procedures (21% at 12 months) [41]. Almost 70% of the patients had diabetes.…”
Section: Discussionmentioning
confidence: 93%
“…In contrast, 12-month follow-up results from the BTK Chill Trial, which evaluated cryoplasty in the infrapopliteal arteries of CLI patients, reported high rates of acute technical success and major amputation-free interval (97.3% and 78.5%, respectively) followed by a low percentage of clinically driven repeat procedures (21% at 12 months) [41]. Almost 70% of the patients had diabetes.…”
Section: Discussionmentioning
confidence: 93%
“…5 In the case above, excellent angiographic and hemodynamic results were achieved in a diffusely diseased ATA with laser atherectomy lesion debulking followed by cryoplasty.…”
Section: Case 2: Cryoplasty For Infrapopliteal Stenosis/occlusionmentioning
confidence: 84%
“…A secondary revascularization procedure within 365 days was performed in 21.0% (17/81) of treated limbs. 5 The Cryoplasty Device: Specification and Basic Technique…”
Section: Cryoplasty In the Peripheral Vasculaturementioning
confidence: 99%
“…28 Follow-up of this initial group was extended and revealed durable results, with freedom from target lesion revascularization of 75% at 1,253 days. 29 The BTK Chill trial studied primary cryoplasty of BTK occlusive disease in CLI patients and yielded similar results. 28 (2) Cutting Balloon Angioplasty Resistant and bifurca- …”
Section: Alternative Angioplasty Technologiesmentioning
confidence: 93%